Impact of Incretin Mimetics on Thyroid Cancer Among Patients with Type 2 Diabetes: A Retrospective Cohort Time-to-Event Analysis - Michael W. Strand; Daniel Chow; Weining Shen; Jonathan H. Watanabe (Pharmacoepidemiology)
Background: Incretin mimetics, including glucagon-like peptide-1 receptor agonists (GLP-1 receptor agonist) and dipeptidyl peptidase-4 (DPP-4) inhibitors, have been increasingly utilized for glycemic control in patients with type 2 diabetes (T2D). Studies have demonstrated additional improvements in weight loss, cardiovascular health, and renal outcomes. Animal studies have shown an association between GLP-1 receptor agonists and C-cell proliferation and elevated calcitonin, resulting in an FDA black box. Insulin resistance in patients with T2D, along with the use of other glucose control medications, confounds the relationship between incretin mimetics and thyroid cancers. The true effect of incretin mimetics on thyroid cancer remains uncertain and speculative due to this confounding. Methods: This retrospective cohort study compared patients with T2D, who were new users of incretin mimetics, to new users of metformin. Study patients used no other anti-diabetes medications beyond the study medications. The risks of incident thyroid cancer and subsequent thyroidectomy were quantified using Cox proportional hazards regression models fitted with adjustments for demographic and medical covariates over a three-year study period. Medullary thyroid cancer (MTC) and multiple endocrine neoplasia type II (MEN2) cases were quantified. Results: Of the 91,394 patients, 28 incretin mimetic users had a diagnosis of thyroid cancer, and nine of these patients underwent a subsequent thyroidectomy procedure. No incretin mimetic user was diagnosed with MTC or MEN2. There was no statistically significant effect on the overall incretin mimetic category (1.28 aHR, 0.83–1.96), the incretin mimetic subcategories of GLP-1 receptor agonists (1.35 aHR, 0.80–2.29), or DPP-4 inhibitor (0.62 aHR, 0.33–1.17) users in developing thyroid cancer within three years of drug initiation. Similarly, no association was found between the overall incretin mimetic category (1.02 aHR, 0.49–2.10), the subcategories of GLP-1 receptor agonists (1.26 aHR, 0.54–2.96), or DPP-4 inhibitors (0.32 aHR, 0.08–1.37) and a subsequent thyroidectomy. Conclusions: In this real-world cohort study, exposure to incretin mimetics overall or through the incretin mimetic subcategories of GLP-1 receptor agonists and DPP-4 inhibitors was not associated with risks of thyroid cancer or thyroidectomy compared to metformin users.